Damage Analysis and Repair of a Small-Scale ORC (Organic Rankine Cycle) Prototype Turbine During Testing - Siburian, Rivaldo; Antonius, Dikky; Abadi , Surjo (Universitas Medan Area, 2025)
This research discusses the damage analysis and repair of an Organic Rankine Cycle (ORC) prototype turbine that experienced failure during testing. The damage occurred due to a collision between the rotor blades and stator blades, causing the rotor blade to break. The primary cause was identified as a manufacturing error in the turbine stator, where the flange holes were misaligned with the shaft. Additionally, the use of improper locking flange bolts and loose fitting on the coupling and stator shaft contributed to this issue. The research methodology included failure analysis using Process Failure Modes and Effects Analysis (PFMEA) to identify potential failures and prioritize corrective actions. The results indicate that adjustments in the manufacturing process, the use of high-precision measurement technology, improved material quality control, and better technician training can significantly reduce the risk of future failures. Furthermore, evaluating operational conditions and conducting regular inspections are recommended to ensure optimal turbine performance. With the implementation of these corrective actions, the ORC turbine prototype is expected to operate more reliably and efficiently during testing and use. This research is expected to make a significant contribution to enhancing the reliability and efficiency of ORC system turbines, and provide guidance for the future development and testing of turbines.